2015
DOI: 10.1039/c5ra05919d
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of NAD(P)H:quinone oxidoreductase 1 (NQO1) inhibitors with novel chemical scaffolds by shape-based virtual screening combined with cascade docking

Abstract: A number of novel NAD(P)H:quinone oxidoreductase 1 (NQO1) inhibitors were discovered from the ChmeDiv database via a simple protocol. Based on two reference NQO1 inhibitors, dicoumarol (DIC) and ES936, shape-based similarity search and cascade docking filtering were conducted to identify new NQO1 inhibitors. Using these techniques, 43 compounds were selected, ordered, and tested. Among them, 7 compounds with novel chemical scaffolds were confirmed to be active by in vitro assays. Determination of the ability f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In the case of DIC ( 2 ) and ES936 ( 6 ), a better understanding of NQO1’s biological functions requires some new scaffolds for NQO1 inhibitors. Using compounds 2 and 6 for reference, Bian et al recently identified compounds 9 – 11 with different chemical scaffolds as NQO1 inhibitors with IC 50 values of 0.92, 2.04, and 1.47 μM, respectively, through a shape-based similarity search and a second cascade docking filtering. By comparing the docked pose of 9 within the NQO1 active site to that of 2 , it was found that the general molecular orientation and the spatial location of 2 and 9 are very similar, and the modifications of fragments A and C in 9 possibly increased its affinity toward NQO1 .…”
Section: Nqo1 Inhibitorsmentioning
confidence: 99%
“…In the case of DIC ( 2 ) and ES936 ( 6 ), a better understanding of NQO1’s biological functions requires some new scaffolds for NQO1 inhibitors. Using compounds 2 and 6 for reference, Bian et al recently identified compounds 9 – 11 with different chemical scaffolds as NQO1 inhibitors with IC 50 values of 0.92, 2.04, and 1.47 μM, respectively, through a shape-based similarity search and a second cascade docking filtering. By comparing the docked pose of 9 within the NQO1 active site to that of 2 , it was found that the general molecular orientation and the spatial location of 2 and 9 are very similar, and the modifications of fragments A and C in 9 possibly increased its affinity toward NQO1 .…”
Section: Nqo1 Inhibitorsmentioning
confidence: 99%
“…Thus, 1 has a wide therapeutic window and exhibits reduced toxicity to normal tissues; this prodrug would benefit from further research on its potential as a specific cancer therapy. Additionally, as an NQO1-responsive prodrug, 1 is expected to be promising in personalized chemotherapy for NQO1-overexpressing cancers when combined with NQO1 diagnostic reagents. , …”
mentioning
confidence: 82%
“…However, Arqule reports that it is a prodrug of β-lapachone. Recently a Chinese group published data on modifications of the base structure that might lead to drug entities with better pharmacological activities, 83 with compound 3k (31) being their best molecule from a solubility and stability aspect. 84 These two papers should be consulted by readers interested in how an initial structure from the late 1890s, may lead to novel pharmaceuticals around a 130 years later.…”
Section: Lapachol and Lapachonementioning
confidence: 99%